Development of a Shape‐Memory Tube to Prevent Vascular Stenosis. Issue 41 (27th August 2019) - Shin, Yong Cheol; Lee, Jung Bok; Kim, Dae‐Hyun; Kim, Taeyoung; Alexander, Grant; Shin, Young Min; Park, Ju Young; Baek, Sewoom; Yoon, Jeong‐Kee; Lee, Yong Jae; Seon, Gyeung Mi; Lee, Mi Hee; et al.
Abstract: Inserting a graft into vessels with different diameters frequently causes severe damage to the host vessels. Poor flow patency is an unresolved issue in grafts, particularly those with diameters less than 6 mm, because of vessel occlusion caused by disturbed blood flow following fast clotting. Herein, successful patency in the deployment of an ≈2 mm diameter graft into a porcine vessel is reported. A new library of property‐tunable shape‐memory polymers that prevent vessel damage by expanding the graft diameter circumferentially upon implantation is presented. The polymers undergo seven consecutive cycles of strain energy‐preserved shape programming. Moreover, the new graft tube, which features a diffuser shape, minimizes disturbed flow formation and prevents thrombosis because its surface is coated with nitric‐oxide‐releasing peptides. Improved patency in a porcine vessel for 18 d is demonstrated while occlusive vascular remodeling occurs. These insights will help advance vascular graft design. Abstract : A new library of property‐tunable shape‐memory polymers (SMPs) is synthesized, and the promising performance of SMP vascular grafting in a porcine femoral artery is demonstrated. New insight into SMP material and diffuser design of small‐diameter vascular grafts is provided, thereby addressing long‐standing issues in deployment‐mediated vessel damage, disturbed flow formation, and blood clotting.